Etika Pemerintahan Berbasis Fiqih Siyasah Di Era Digital - Mustafid, Mustafid (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2024)
This study examines government ethics based on fiqih siyasah in the digital era. The type of research is library research with a qualitative approach, primary data sources from fiqh siyasah, and secondary data from books, journal articles, and so on. Data collection techniques used the documentation method, then analyzed using descriptive qualitative techniques. The result of this research is that technological developments are so rapid and impact social and political life that it is necessary to apply the principles of siyasa fiqh to create an Islamic government ethic. To get there, it is necessary to have an ethical government based on fiqih siyasah in the digital era, namely by implementing: Islamic principles, using technology by Islamic values, data security and privacy, transparency and public participation, public services, collaboration and consultation with Islamic scholars. It will impact government, namely being able to create governance that is more just, fair, and by Islamic religious values, and can improve the quality of public services and community involvement in the decision-making process.